Pulmonary Mucinous Adenocarcinoma - A. Yu. Usacheva; N. K. Silanteva; A. P. Petrosian; V. S. Usachev; A. V. Sidorin; S. A. Ivanov (Вестник рентгенологии и радиологии)
Mucinous adenocarcinoma is a rare malignant tumor of the lung, which is accompanied by extremely scarce and nonspecific symptoms. This leads to an increase in the timing of its recognition, especially in young women. Given the poor prognosis of the pathlogy, the problem of its early diagnosis with histological and immuno-histochemical studies is extremely urgent. The presented clinical case demonstrates the possibilities of computed tomography with intravenous contrast enhancement in a young woman for the diagnosis of mucinous lung adenocarcinoma.